Improvement of the Knowledge and Attitudes of Health Cadres in Eliminating Stigma and Discrimination Regarding HIV and or Tuberculosis - Heny Arwati; Shafira Meidyana; Raudia Faridah Humaidy; Soraya Isfandiary Iskandar; Adikara Pagan Pratama; Rabhindra Javier Hariri Darussalam; Ayu Nazilla Fatimahtuz Zahra; Linda Dewanti (Journal of Community Medicine and Public Health Research, 2026)
HIV and or TB-related stigma frequently discourages people from seeking healthcare, which can lead to delayed diagnosis and poor health outcomes. The aim of this study is to analyze cadres' knowledge and attitudes regarding diseases to eliminate stigma in their community. Thirty health cadres in a primary healthcare setting in Surabaya were recruited as participants after getting informed consent. Participants were trained in the transmission, prevention, and treatment of diseases, followed by a role-play and a Focus Group Discussion. Pre- and post-tests were conducted to assess cadres' knowledge and attitudes. After the intervention, understanding of HIV and TB among cadres increased significantly (p < 0.001), from pre-test scores of 82.7 ± 17.9 (HIV) and 81.1 ± 6.6 (TB) to 95.7 ± 4.9 (post-HIV test) and 89.3 ± 10.5 (post-TB test). After interventions, cadres understand that HIV transmission can occur from mother to fetus, during childbirth, and through breast milk; and that HIV is not transmitted through air, water, eating utensils, toilet seats, sweat, tears, shaking hands, and hugging. They also understand that most TB patients are no longer contagious after 2 months of treatment and can be cured after 6 months. In the focus group discussion, cadres shared about cases of stigma and discrimination that they had encountered. Finally, together with primary healthcare, they plan to disseminate these results within their community through various activities (sub-district, district, and school) to stop stigma and discrimination.